In formation Provessing and its relation to the performance of scrolling skillfrom the top and bottom of the volley ball to the students - تمارة احمد ياس أ. د. مواهب حميد نعمان (physical education and sport sciences college for women/ Baghdad University, 2020)
The problem of research is that there are differences between learners in processing in formation in general and there is variation at the learners level perform scrolling skill of the passes up and down by the volley ball .Therefore the researchers decided to conduct astudy through which identify the relationship between information processing and the skill of scrolling from the top and bottom by the volleyball. The researchers used the descriptive approach by themethod of interconnectivity .Asampleconsist of21 students from first staye in collage of physical education and sports science for Girls(university of Baghdad) and attest has been applied(process information and scroll up and down) on the research sample after the required statistical treatments , Anumber of conclusiow were reached. The most important one was that the pro cessing of the information is related to the per formance of the scrolling skill from the top and bottom of the volley ball in the sample of the research